The effect of mandala colouring on anxiety in hospitalized COVID‐19 patients: A randomized controlled clinical trial. (18th June 2021) - Khademi, Fatemeh; Rassouli, Maryam; Rafiei, Fatemeh; Moayedi, Siamak; Torres, Mercedes; Marzban, Negin; Haji, Ensieh; Golitaleb, Mohamad
Abstract: COVID‐19 significantly affects patients' mental health, triggering a wide range of psychological disorders, including anxiety. The aim of this study was to investigate the effect of mandala colouring on the anxiety of hospitalized COVID‐19 patients. In this randomized controlled clinical trial, 70 hospitalized patients with COVID‐19 were randomly divided between the intervention and control groups. Standard care was provided for both groups. The intervention group spent 30 min/day for six consecutive days performing mandala colouring. Patient anxiety was measured prior and subsequent to the intervention in both groups using the Spielberger State‐Trait Anxiety Inventory. Data were analysed using SPSS software version 25. The mean anxiety score was not significantly different between the two groups before the intervention ( P  = 0.08). Subsequent to the intervention, the mean anxiety score in the intervention and control groups was 44.05 ± 4.67 and 67.85 ± 6.25, respectively, indicating a statistically significant ( P  = 0.0001) decrease in the anxiety measured among the intervention group as compared with that of the control group. The results of this study show that 30 min of mandala colouring daily is an effective strategy for reducing anxiety in hospitalized COVID‐19 patients. Mandala colouring can complement routine treatment and provides a non‐pharmaceutical option for decreasing patient anxiety.